Despair (Quranic study) - Fatima Ahmed Mahmud Al Haj Hasan (My University, 2011)
This study is a Quranic one and a step towards the objective interpretation of the Holy Quran in which the researcher discussed the issue of Despair through verses from the Holy Quran. The study is divided into 4 chapters, an introduction and a conclusion. In the introduction, the researcher talked about the importance of this study and highlighted its significance through discussing the global enmity and deception that the Islamic nation faces these days which yielded many difficulties and crises that increased depression and Despair among the Muslim population around the world. In chapter one, the researcher discussed the definition of Despair in language, dictionary and in the Quranic context, while in the second chapter the researcher talked about the different faces of Despair and the position of prophets towards it. In the third chapter, the researcher explained the reasons behind Despair and the punishment and destiny of hopeless people. The fourth chapter included an explanation of the possible ways of prevention and treatment that can protect the human being from the evils and negative impacts of Despair. The researcher referred to interpretation books, Hadith, ethics books, language and translations to conduct her research with a special focus on interpretation books and the statements made by Muslim interpreters and scholars. In the conclusion, the researcher included a number of results that the study yielded: 1- There is a close relationship between blasphemy (Kufr) and Despair and that the person who surrenders to Despair is the one whose heart is no longer filled with belief in God; he who becomes a disbeliever is the one who has become hopeless of his connection with Allah. 2- The mentioning of Despair in the Holy Quran came under the meaning of “Despair”, except in Al-Ra’ed verse where it came under the meaning of “Knowledge”. 3- Committing sins is enough to trick a human being into falling into the illusions of Despair and despair in case he does not repent and return back to Allah.

هذه الرسالة دراسة قرآنية، وهي خطوة على طريق التفسير الموضوعي للقرآن الكريم، تناولت موضوع اليأس من خلال آيات القرآن الكريم، وقد قُسِّمَتْ إلى أربعة فصول، ومقدمة وخاتمة، كان الحديث في المقدمة عن أهمية هذه الدراسة، وإبراز قيمتها من خلال الحديث عن ما يواجه الأمة الإسلامية من مكر وعداء عالمي، صنع محناً وصعوبات سرَّعت في ظهور اليأس والإحباط بين أبناء هذه الأمة، وأما بالنسبة للفصول، فقد كان الفصل الأول منها يدور حول معنى اليأس في اللغة والاصطلاح والسياق القرآني، ثم يليه الفصل الثاني بعنوان: صور اليأس وموقف الأنبياء منه، وحمل الفصل الثالث منها أسباب اليأس وجزاء اليائسين، أما الفصل الرابع فقد حوى سبل الوقاية والعلاج التي تحمي الإنسان من شرور اليأس وأضراره. وكانت كتب التفسير والحديث والأخلاق واللغة والتراجم هي الكتب والمراجع المعتمدة في هذه الرسالة، مع التركيز على كتب التفسير وأقوال المفسرين من علماء هذه الأمة. وتضمنت الخاتمة عدة نتائج، منها: 1- أن هناك علاقة وثيقة، وتلازماً قوياً بين الكفر واليأس؛ ذلك أنه لا ييأس الإنسان من رحمة الله إلا حين يكفر قلبه، وينقطع ما بينه وبين ربه، وكذلك هو لا يكفر إلا وقد يئس من اتصال قلبه بالله، ولم يَعُدْ له إلى رحمة الله سبيل. 2- أن كل ما جاء في القرآن الكريم من يأس فهو بمعنى القنوط، إلا آية الرعد (أفلم ييأس الذين آمنوا أن لو يشاء الله لهدى الناس جميعا)، جاءت بمعنى: العلم. 3- أن ارتكاب المعاصي والذنوب كفيل بأن يوقع الإنسان في أوهام اليأس والقنوط، في حال عدم توبته، وعدم رجوعه إلى الله سبحانه وتعالى.
(اليأس (دراسة قرآنية